Duration of diabetes-related complications and mortality in type 1 diabetes: a national cohort study. (16th January 2021) - Bjerg, Lasse; Gudbjörnsdottir, Soffia; Franzén, Stefan; Carstensen, Bendix; Witte, Daniel R; Jørgensen, Marit E; Svensson, Ann-Marie
Abstract: Background: People with type 1 diabetes often live for many years with different combinations of diabetes-related complications. We aimed to quantify how complication duration and total complication burden affect mortality, using data from national registers. Methods: This study included 33 396 individuals with type 1 diabetes, registered in the Swedish National Diabetes Register at any time between 2001 and 2012. Each individual was followed and classified according to their time-updated diabetes-related complication status. The main outcomes were all-cause mortality, cardiovascular (CV) mortality and non-CV mortality. Poisson models were used to estimate the rate of these outcomes as a function of the time-updated complication duration. Results: Overall, 1748 of the 33 396 individuals died during 198 872 person-years of follow-up. Overall, the time-updated all-cause mortality rate ratio (MRR) was 2.25 [95% confidence interval (CI): 1.99–2.54] for patients with diabetic kidney disease, 0.98 (0.82–1.18) for patients with retinopathy and 4.00 (3.56–4.50) for patients with cardiovascular disease relative to individuals without complications. The excess rate was highest in the first period after a diagnosis of CVD, with an 8-fold higher mortality rate, and stabilized after some 5 years. After diagnosis of diabetic kidney disease, we observed an increase in all-cause mortality with an MRR of around 2 compared with individuals without diabetic kidney disease, which stabilized after few years. Conclusions: In this cohort we show that duration of diabetes-related complications is an important determinant of mortality in type 1 diabetes, for example the MRR associated with CVD is highest in the first period after diagnosis of CVD. A stronger focus on time-updated information and thorough consideration of complication duration may improve risk stratification in routine clinical practice.